Indian Endodontic Society: Position statement on the management of separated instruments during root canal treatment - Aishwarya Vasudevan; Sanjay Miglani; Vivek Hegde; Velayutham Gopikrishna (Wolters Kluwer Medknow Publications, 2024)
This position statement on the management of separated instruments, endorsed by the Indian Endodontic Society, aims to provide a brief perspective on the challenges faced during shaping of the complex root canal system, and how the inadvertent separation of a broken instrument must be dealt with. The need for referral of such cases to specialist endodontists who are trained to use advanced instrument retrieval systems with the aid of the dental operating microscope is also highlighted.